Physical and thermal properties of treated sugar palm/glass fibre reinforced thermoplastic polyurethane hybrid composites - Atiqah A.; Jawaid M.; Sapuan S.M.; Ishak M.R.; Ansari M.N.M.; Ilyas R.A. (Elsevier Editora Ltda, 2023)
Glass fibers; Physical properties; Polyurethanes; Textile fibers; Water absorption; Automotive component; Fibre reinforced; High performance composites; Hybrid composites; Polyurethane hybrids; Thickness swelling; Thermodynamic properties